Biblioshiny Mapping of Corporate Governance in Islamic Banking Research: A Last Decade Review - Chitra Yuliashri Katili; Kadir, Rifadli D. (Mutanaqishah: Journal of Islamic Banking, 2024)
A study on corporate governance in Islamic Banking has developed. This study attempts to map the development of this research over the past decade. Using 111 articles from the Scopus database with Biblioshiny R-studio analysis, mapping was carried out related to the document. The study found a fluctuation in the number of publications on this topic, with Grassa R as the most impactful author, Universiti Teknologi Petronas as the affiliate that published the most articles, and the United Kingdom as the most cited country. Research on this topic can still be developed by considering issues that have been studied previously, such as its relationship to Financial Performance and Shariah Governance.